Ethnicity as mobilization infrastructure: Pashtun identity and taliban insurgency in Afghanistan - Muhammad Hayyi’ Lana Alkhan; Akbar Farid; Ahmad Fauzi; Zikri Rahmani (Priviet Social Sciences Journal, 2026)
This study examines the role of Pashtun ethnicity in Taliban insurgency and post-2021 governance by conceptualizing ethnicity as mobilization infrastructure rather than as a primordial or deterministic cause of conflict. Drawing on a critical narrative review of recent scholarly and policy-oriented literature, this study analyzes how Pashtun identity operates through social networks, territorial ties, normative frameworks, and organizational continuity to enable recruitment, coordination, legitimacy, and political control. The findings show that Pashtun ethnicity has facilitated the Taliban’s organizational resilience and its transition from insurgency to governance, particularly through network-based mobilization and access to territorial sanctuaries. Simultaneously, the selective use of Pashtunwali has contributed to local legitimacy in Pashtun-majority areas while constraining broader national acceptance. The analysis further highlights the dual effect of ethnic dominance in the post-2021 political order: strengthening short-term stability and internal cohesion while exacerbating political exclusion and ethnic grievances. By specifying the mechanisms through which ethnic identity is transformed into mobilization capacity, this article contributes a mechanism-based framework to debates on ethnicity, insurgency, and governance in Afghanistan, offering a non-deterministic and analytically grounded understanding of conflict dynamics in multiethnic societies.